Educational Philosophy of Swami Vivekananda and the Bengali Bhadralok’s search for cultural identity during the second half of the Nineteenth Century (Paramita: Historical Studies Journal, 2021)
The British government introduced Western education first in Bengal during the nineteenth century to produce clerks to run the administration cheaply and create a group of loyal servants. However, the educated Bengali bhadralok or the elites of Bengali society, who emerged as a renter class during the British period, soon became the object of racist ridicule by the British. As a result, a critique against blind imitation of western civilization was developed among a section of the Hindu Bengali bhadralok. In the light of these developments, this article tries to evaluate the educational ideas of Swami Vivekananda (original name Narendranath Datta, 1863-1902), a great Hindu monk of India, and attempts to find out how his educational philosophy contributed to the socio-cultural rejuvenation of the Bengalis. This article found that his critique of the colonial educational policy and his ideas on Man-making education enlightened the Bengalis and contributed significantly to the national awakening of the Indians. Moreover, his educational philosophy does not lose its validity even today.Pemerintah Inggris memperkenalkan pendidikan Barat pertama kali di Bengal selama abad kesembilan belas untuk menghasilkan juru tulis untuk menjalankan administrasi dengan murah dan menciptakan sekelompok pelayan yang setia. Namun, bhadralok Bengali terpelajar atau elit masyarakat Bengali, yang muncul sebagai kelas penyewa selama periode Inggris, segera menjadi objek ejekan rasis oleh Inggris. Akibatnya, kritik terhadap tiruan buta peradaban barat dikembangkan di antara bagian bhadralok Hindu Bengali. Berdasarkan perkembangan tersebut, artikel ini mencoba mengevaluasi gagasan pendidikan Swami Vivekananda (nama asli Narendranath Datta, 1863-1902), seorang biksu Hindu besar India, dan mencoba untuk mengetahui bagaimana filsafat pendidikannya berkontribusi pada sosial- peremajaan budaya Bengali. Artikel ini menemukan bahwa kritiknya terhadap kebijakan pendidikan kolonial dan ide-idenya tentang pendidikan penciptaan manusia mencerahkan orang Bengali dan berkontribusi secara signifikan pada kebangkitan nasional orang India. Selain itu, filosofi pendidikannya tidak kehilangan validitasnya bahkan hingga hari ini.